Angle‐, Polarization‐, and Wavelength‐Resolved Light Scattering of Single Mie Resonators Using Fourier‐Plane Spectroscopy. Issue 8 (15th February 2021) - Hinamoto, Tatsuki; Hamada, Mikihiko; Sugimoto, Hiroshi; Fujii, Minoru
Abstract: Interference between multipole modes of Mie resonance provides the possibility to tailor a radiation pattern of a subwavelength optical resonator. Unidirectional scattering arising from constructive and destructive interferences between electric and magnetic dipolar modes in a nanoantenna allows to design a variety of metasurfaces. However, experimental determination of radiation patterns of an individual nanoobject and the decomposition into multipoles have not been performed under plane wave illumination due to the inability of angular analysis in a conventional optical microscope. To this end, an angle‐, polarization‐, and wavelength‐resolved microscopy setup is developed in this work to measure radiation patterns of an individual nanoobject. A single spherical silicon nanosphere is employed as an ideal Mie resonator and the angle‐ and polarization‐resolved scattering is measured in the angular range from 30° to 150° against the incident angle. It is shown that Mie scattering from the electric and magnetic dipoles of a single silicon nanosphere is selectively measured in the setup. Abstract : In combination with tailored dark‐field illumination and Fourier plane spectroscopy, angle‐resolved scattering measurement of individual nanoobjects is presented. By employing a silicon nanosphere as an ideal scatterer, an analysis of directional scattering arising from the interference of Mie resonances is demonstrated. Moreover, by further resolving in polarization, the developed method is able to separately measure electric and magnetic dipolar scatterings.